En defensa del “argumento maestro” de Berkeley - Prado Velásquez, Alvaro Antonio (2023)
Berkley’s so-called “master argument”—through which he proves his principle esse est percipi—has been submitted to mixed criticisms by various commentators. Some defend its validity from the perspective of their own interpretations, while some claim that the argument is fallacious due to several objections. This article defends the master argument against three objections raised by Russell, Pitcher and Tipton. These could be respectively characterized as “the objection of the confusion of the perceptive act with the perceived object”, “the objection of the confusion of the concept of the object with the object itself”, and “the objection of the solipsism of the present”. I present my own reading of the master argument in order to avoid misunderstandings and claim that the correct understanding of this argument requires considering the following issues: the clarification of the Berkeleyan concepts of idea and perception; the explication of the intentionality of perception, understood as its intentional direction towards intentional objects (ideas); and the distinction between two levels of intentional direction of mediated experience (of an idea through another one)—that is, a level directed towards the concept or mental representation as its immediate intentional object, and another level directed towards the represented object as its mediated intentional object.